A Solution‐Mediated Pathway for the Growth of the Solid Electrolyte Interphase in Lithium‐Ion Batteries (Adv. Energy Mater. 14/2023). Issue 14 (13th April 2023) - Esmaeilpour, Meysam; Jana, Saibal; Li, Hongjiao; Soleymanibrojeni, Mohammad; Wenzel, Wolfgang
Abstract : Solid Electrolyte Interphase In article number 2203966, Wolfgang Wenzel and co‐workers use a mesoscale simulation approach to comprehensively characterize the growth and composition of the solid electrolyte interphase (SEI) based on a chemistry‐specific reaction network. They find that the organic SEI forms and grows in a solution‐mediated pathway by the aggregation of SEI precursors far away from the surface via a nucleation process, which has consequences for long‐term battery operation.